2019
DOI: 10.4269/ajtmh.18-0635
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Biomarker Profiles Distinguish Malawian Children with Malarial and Non-malarial Sepsis

Abstract: Presently, it is difficult to accurately diagnose sepsis, a common cause of childhood death in sub-Saharan Africa, in malaria-endemic areas, given the clinical and pathophysiological overlap between malarial and non-malarial sepsis. Host biomarkers can distinguish sepsis from uncomplicated fever, but are often abnormal in malaria in the absence of sepsis. To identify biomarkers that predict sepsis in a malaria-endemic setting, we retrospectively analyzed data and sera from a case-control study of febrile Malaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
2
1
Order By: Relevance
“…Parasitic infections, which are frequently found in LMIC, did not influence CRP levels; hence there would be no need to rule out these infections to interpret the results of CRP. On the other hand, in accordance with previous evidence [ 7 , 12 ], malaria increased CRP, though to levels that were significantly lower than those found in bacterial infections. Malaria RDTs are systematically used in acute febrile illnesses in malaria-endemic countries.…”
Section: Discussionsupporting
confidence: 92%
“…Parasitic infections, which are frequently found in LMIC, did not influence CRP levels; hence there would be no need to rule out these infections to interpret the results of CRP. On the other hand, in accordance with previous evidence [ 7 , 12 ], malaria increased CRP, though to levels that were significantly lower than those found in bacterial infections. Malaria RDTs are systematically used in acute febrile illnesses in malaria-endemic countries.…”
Section: Discussionsupporting
confidence: 92%
“…These results might be due to studies that focused solely on microscopy failed to consider low density infected patients who had elevated IL-6 separately, further reducing the significance between uncomplicated malaria and febrile controls, as febrile control groups were not truly Plasmodium negative or with submicroscopic infection. Nevertheless, the meta-analysis results were in contrast to a case-controlled study that demonstrated patients with malarial fever had higher IL-6 levels than those with non-malaria fever 66 , indicating the increase in IL-6 levels might be specific for malaria compared to other febrile diseases. Previous studies showed that IL-6 concentrations in healthy individuals were typically low; that is, in the range of 0.2–7.8 pg/mL 67 .…”
Section: Discussioncontrasting
confidence: 84%
“…22 Furthermore, concomitant conditions like HIV infection and malnutrition could influence the expression of biomarkers, for example, lowering CRP concentrations, thus potentially causing bacterial infections being underdiagnosed and undertreated. 23 Conversely, some biomarkers, CRP in particular, can be elevated in case of malaria, 24 which makes it impossible to rule out or rule in other infections in patients with concomitant malaria infection.…”
Section: Discussionmentioning
confidence: 99%